ANALISIS RAWAN KEKERINGAN LAHAN PADI KABUPATEN BANYUWANGI JAWA TIMUR - Nuryadi Nuryadi; Suci Agustiarini (Unit Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Meteorologi Klimatologi dan Geofisika, 2019)
In general, the definition of drought is the availability of water that is less than the need for water for the necessities of life, agriculture, economic activity, and environment. Associated with food production, agricultural drought is very influential on cultivation activities on food production in a region. Groundwater availability is essential to determine the level of drought-prone rice fields in Banyuwangi District. The data used are monthly rainfall period 1981-2010 from 32 rain post and BKMG station in Banyuwangi Regency. Drought level analysis using available groundwater weighting and Oldeman climate type on each rain post. Banyuwangi Regency based on Oldeman climate classification is divided into 9 climate types ranging from wet climate (B1) to dry (D and E). In February, March, and April the availability of ground water is higher than in other months, whereas August, September and October have the lowest groundwater availability. The western part of Banyuwangi has more water available than the eastern part. The degree of dryness of paddy land varies temporally and spatially from very vulnerable to safe. The dry and prone levels of peak rice dryness occur in September and October with the widest coverage of the area. Most of the areas experiencing safe levels for paddy fields are in January, February, March and April.